2021
DOI: 10.3906/sag-2006-203
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic alterations in patients with Covid-19

Abstract: Background/aim: Coronavirus 2019 disease (Covid-19) was first seen in December 2019 and afterwards it became a pandemic. Several systemic involvements have been reported in Covid-19 patients. In this study, it was aimed to investigate the cerebrovascular hemodynamics in patients with Covid-19. Materials and methods: The sample of this study was conducted on 20 patients hospitalized in our clinic diagnosed with Covid-19 via PCR modality and 20 healthy volunteers of similar age and sex. Bilateral middle cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…The role of TCD-derived parameters (mCBFV, PI, eICP, and eCPP) for the assessment of cerebral hemodynamics in critically ill patients without a primary brain injury is well established, with relevant data on the role of altered autoregulation in the pathogenesis of septic encephalopathy [45] or of reduced mCBFV in association with severe post-anoxic brain damage [46], although the association with long-term neurological outcome needs to be further evaluated. In hospitalized COVID-19 patients, higher mCBV and lower vasoreactivity were observed than in matched healthy volunteers [47]. Additionally, in a small recent study using cerebral ultrasound, eICP was higher and diastolic CBFV lower in COVID-19 patients developing neurological complications when compared to others [40].…”
Section: Discussionmentioning
confidence: 93%
“…The role of TCD-derived parameters (mCBFV, PI, eICP, and eCPP) for the assessment of cerebral hemodynamics in critically ill patients without a primary brain injury is well established, with relevant data on the role of altered autoregulation in the pathogenesis of septic encephalopathy [45] or of reduced mCBFV in association with severe post-anoxic brain damage [46], although the association with long-term neurological outcome needs to be further evaluated. In hospitalized COVID-19 patients, higher mCBV and lower vasoreactivity were observed than in matched healthy volunteers [47]. Additionally, in a small recent study using cerebral ultrasound, eICP was higher and diastolic CBFV lower in COVID-19 patients developing neurological complications when compared to others [40].…”
Section: Discussionmentioning
confidence: 93%
“…2). Recently studies revealed dysregulation of coagulation factors, as a function of circulating IL-6 levels and altered cerebral hemodynamics [22,23], which probably contributed to headaches during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…34 The role of TCD-derived parameters (mCBFV, PI, eICP and eCPP) at the assessment of cerebral hemodynamics in critically ill patients without a primary brain injury is well established, with relevant data on the role of altered autoregulation in the pathogenesis of septic encephalopathy 35 or of reduced mCBFV in association with severe post-anoxic brain damage, 36 although the association with long-term neurological outcome needs to be further evaluated. In hospitalized COVID-19 patients higher mCBV and lower vasoreactivity were observed than in matched healthy volunteers 37 . Also, in a small recent study using cerebral ultrasound eICP was higher and diastolic CBFV lower in COVID-19 patients developing neurological complications when compared to others 38 .…”
Section: Discussionmentioning
confidence: 95%